If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -6 = 3x Reorder the terms: -6 + 15x = 3x Solving -6 + 15x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -6 + 15x + -3x = 3x + -3x Combine like terms: 15x + -3x = 12x -6 + 12x = 3x + -3x Combine like terms: 3x + -3x = 0 -6 + 12x = 0 Add '6' to each side of the equation. -6 + 6 + 12x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 12x = 0 + 6 12x = 0 + 6 Combine like terms: 0 + 6 = 6 12x = 6 Divide each side by '12'. x = 0.5 Simplifying x = 0.5
| 7.6/0.2 | | y=2596+832x | | (a+7)8-3a= | | 4.5x+45.8=8.6-7.9x | | (a-5)+7=-(8+3a) | | X=2x^2-3x+4 | | -7x(4x+2)-5(3x-9)=5(3x+6) | | 6/5+2/5x=21/10+5/2x+1/2 | | f(25)=0.15 | | 12x=1-(-11) | | 13/8+1/5t=2 | | 5+5x-4=9x+22-7x | | 2*9+8= | | 4x+31=18 | | 26/25= | | 4/9x=1/7 | | (8x+8)+(8x-2)= | | y=-1/8x-3/8 | | 7.94*10^-3=(x^2)/(0.5-x) | | 1900-6x=100 | | (X+5)=x^2+kx+30whatisk | | 8w-15w=-63 | | 13.37=-4.9t^2+35t | | 2x^2+4xy+3xy+3y^2=0 | | 9.32=-4.9t^2+35t | | 5(t-3)+7= | | x^2-10x+21=45 | | 44+b=-32 | | 7/9-1/10 | | Cos(64)x=16 | | 7.14=7t^2+35t | | Cos(64)=16 |